1988
DOI: 10.1080/00913847.1988.11709555
|View full text |Cite
|
Sign up to set email alerts
|

A Physiologic Profile Comparing Levels and Styles of Female Dancers

Abstract: In brief: A physiologic profile comparing 39 female dancers was undertaken to better understand the factors distinguishing four levels and styles of dance: professional ballet (PB), professional modern, university ballet, and university modern. The PB dancers had significantly lower VO2 max values on the tread-mill as well as lower peak blood lactate levels following the Wingate test for anaerobic capacity than the other dancers. The PB dancers also had a significantly higher isokinetic hamstring-quadriceps ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 19 publications
5
43
0
Order By: Relevance
“…In all these aforementioned studies, the total number of dance students derived from both ballet and modern dance training. In other studies, however, which indeed separated the dance students into ballet and contemporary, no signifi cant diff erences were found either in % BF or FFM between these two dance styles [13,50] . Signifi cant lower % BF values were instead found in professional contemporary dancers compared to beginner dance students [12] .…”
Section: Body Compositionmentioning
confidence: 95%
See 3 more Smart Citations
“…In all these aforementioned studies, the total number of dance students derived from both ballet and modern dance training. In other studies, however, which indeed separated the dance students into ballet and contemporary, no signifi cant diff erences were found either in % BF or FFM between these two dance styles [13,50] . Signifi cant lower % BF values were instead found in professional contemporary dancers compared to beginner dance students [12] .…”
Section: Body Compositionmentioning
confidence: 95%
“…Non signifi cant diff erences were also detected in anaerobic mean power between adolescent dance students compared to either recreational dancers or non-dancers [38] . Signifi cant diff erences were instead depicted in post exercise blood lactate levels, where professional contemporary dancers exhibited higher values than their ballet counterparts [13] . By investigating the eff ects of supplementary exercise training on jumping ability and dance performance [11,25] , these recent studies form the only known examples where aspects of fi tness and contemporary dance performance were simultaneously considered.…”
Section: Aerobic / Anaerobic Fi Tnessmentioning
confidence: 98%
See 2 more Smart Citations
“…Previously published data on the levels of physical fitness of dancers and the physiological response during dancing focused mainly on modern and ballroom dancing, ballet, and aerobic dance workouts [3][4][5][6][7][8][9][10][11][12][13]. These studies found that the aerobic fitness level of dancers can be considered as average and characteristic of individuals practicing non-endurance sports [3,5,9,13]. These results may be due in part to the specific nature of the types of dance that were observed, whose movement sequences, although dynamic, can be considered short-lasting with energy provided by the phosphagen (ATP and phosphocreatine) and anaerobic (glycolytic) systems.…”
Section: Introductionmentioning
confidence: 99%